EXAMINING FORENSIC ACCOUNTING'S ROLE IN SAFEGUARDING INDIAN BANKING INTEGRITY - Amnaa Jamal; Harjit Singh (Фінансово-кредитна діяльність: проблеми теорії та практики)
Economic sustainability is indispensable for achieving inclusive growth in the Indian banking sector. A sustainable, robust, and healthy banking system keeps a country rolling on its economic wheels. This research study highlights much-talked-about but less-understood aspects of forensic accounting in the Indian banking sector. It examines forensic accounting's impact on the performance of public and private sector banks. The perspectives of bank managers and officers working in the Delhi National Capital Region (NCR) are the primary focal points of this study. Furthermore, the research paper emphasised the importance of shedding light on the benefits. Its Findings suggest that the demand for forensic accountants will also increase with the adoption of forensic accounting practices in India. Since forensic accounting is still optional, most accounting professionals don’t practice forensic accounting. Therefore, there is a need to spread awareness among accounting professionals about adopting Forensic Accounting Practices. This will also add sustainable corporate governance and make forensic accounting a required component of the governance system.